2008
DOI: 10.1038/ncb1806
|View full text |Cite
|
Sign up to set email alerts
|

Activation of TGF-β/activin signalling resets the circadian clock through rapid induction of Dec1 transcripts

Abstract: The circadian clock is reset by external time cues for synchronization to environmental changes. In mammals, the light-input signalling pathway mediated by Per gene induction has been extensively studied. On the other hand, little is known about resetting mechanisms that are independent of Per induction. Here we show that activation of activin receptor-like kinase (ALK), triggered by TGF-beta, activin or alkali signals, evoked resetting of the cellular clock independently of Per induction. The resetting was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
133
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(139 citation statements)
references
References 35 publications
6
133
0
Order By: Relevance
“…Further investigation by us will be directed towards further addressing the mechanism. Kon et al (31) along with our previous study demonstrated that DEC1, as a downstream target gene, was induced by transforming growth factor-β (TGF-β) and tumor necrosis factor-α (TNF-α) (32). TNF-α and TGF-β were widely reported as regulators in epithelial-mesenchymal transition (EMT) through activation of NF-κB and TGF-β signal pathway, respectively (11,33).…”
Section: Discussionmentioning
confidence: 97%
“…Further investigation by us will be directed towards further addressing the mechanism. Kon et al (31) along with our previous study demonstrated that DEC1, as a downstream target gene, was induced by transforming growth factor-β (TGF-β) and tumor necrosis factor-α (TNF-α) (32). TNF-α and TGF-β were widely reported as regulators in epithelial-mesenchymal transition (EMT) through activation of NF-κB and TGF-β signal pathway, respectively (11,33).…”
Section: Discussionmentioning
confidence: 97%
“…7, E-K), suggesting that BMAL2 plays a more important role in a regulatory loop than that in the core loop. Bmal2 might be an important gene as well for clock resetting, like Dec1 (29).…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49][50] Conversely, several studies have demonstrated at a molecular level how these intracellular signaling mediators contribute to circadian regulation. For example, in mammals, glycogen synthase kinase-3b (GSK-3b), the key kinase regulating the Wnt signaling pathway, phosphorylates CRY2 and PER2 and thereby controls CRY2 protein stability and PER2 subcellular localization.…”
Section: Possible Crosstalk Between the Circadian Clock And Cellular mentioning
confidence: 99%
“…48,51) Another example is the stimulation of Dec1 gene expression that is induced by the TGF-b/activin signaling pathway during alkaline shockinduced entrainment of mammalian peripheral clocks. 49) The signaling pathways involving these mediators play essential roles in development, proliferation, DDR, and cell death processes, suggesting that these processes and the circadian clock are separate nodes of a common regulatory network. In support of this idea, a recent study in zebrafish has revealed that the same MAPK signaling cascades are involved in both DDR and the light-dependent pathways responsible for entrainment of the circadian clock 52) (see below).…”
Section: Possible Crosstalk Between the Circadian Clock And Cellular mentioning
confidence: 99%